Pandemic and beyond : phishing in a larger pond - Yang, Jennifer Hui (2020)
The greatly increased reliance on technology for work, education, business, and social interaction during the COVID-19 pandemic has opened up opportunities for cyber criminals. It is highly probable that post-COVID-19, this reliance will lead to a hyperconnected world.